Niveles de torta de maracuyá (Passiflora edulis) y su efecto en la alimentación de pollos pio pio - Murillo Dicao, Tomas David (2015)
This research was conducted in the Zapotal enclosure located northwest of Canton Quinindé Esmeraldas Province 16 kilometers from the city of Quinindé, geographical cordenadas were 0 ° 30 '0' 'and 79 ° 30' 0 '' of O length and lasted 60 days. They settled the objective evaluate passion fruit cake (Passiflora edulis) and its effect on chicken feed Pio Pio. An experimental design totally at random (DCA) with four treatments and four replicates with four levels of passion fruit cake 0%, 2.5%, 5% and 7.5% of passion fruit cake was used. During the field research were evaluated as variables; weight of chickens (g), weight gain (g), feed intake (g), feed conversion, carcass weight (g) data were taken at 10, 20, 30, 40, 50 and 60 days and total values. Besides the cost benefit was calculated. As a result it was found that the T4. (7.5% of passion fruit cake) leads to the best results, with a weight gain of 2450.21g .; Total food consumption of 6273.75 g .; a feed conversion of 2.56 and a carcass weight 2122.94g. The best relationships were Benefit Cost for T4 treatment. (7.5% of passion fruit cake) and T3. (5% of passion fruit cake).